2010
DOI: 10.1017/s0003055410000286
|View full text |Cite
|
Sign up to set email alerts
|

International System and Technologies of Rebellion: How the End of the Cold War Shaped Internal Conflict

Abstract: Because they are chiefly domestic conflicts, civil wars have been studied primarily from a perspective stressing domestic factors. We ask, instead, whether (and how) the international system shapes civil wars; we find that it does shape the way in which they are fought—their “technology of rebellion.” After disaggregating civil wars into irregular wars (or insurgencies), conventional wars, and symmetric nonconventional wars, we report a striking decline of irregular wars following the end of the Cold War, a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
352
1
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 551 publications
(366 citation statements)
references
References 43 publications
6
352
1
7
Order By: Relevance
“…This example also illustrates that the technological mechanism underlying the LAG is not restricted to interstate conflict, but applies to civil war as well, especially when heavy weapons are used. As Kalyvas and Balcells (2010) observe, so called ''symmetric non-conventional'' and ''conventional'' tactics have played an increased role since the end of the Cold War in civil conflicts. In their empirical analysis, Kalyvas and Balcells (2010) found that access to heavy weaponry for rebel forces early on in civil conflicts significantly increased after the end of the Cold War.…”
Section: Technological Aspectsmentioning
confidence: 99%
“…This example also illustrates that the technological mechanism underlying the LAG is not restricted to interstate conflict, but applies to civil war as well, especially when heavy weapons are used. As Kalyvas and Balcells (2010) observe, so called ''symmetric non-conventional'' and ''conventional'' tactics have played an increased role since the end of the Cold War in civil conflicts. In their empirical analysis, Kalyvas and Balcells (2010) found that access to heavy weaponry for rebel forces early on in civil conflicts significantly increased after the end of the Cold War.…”
Section: Technological Aspectsmentioning
confidence: 99%
“…This relationship may partially explain the widespread occurrence of lengthy civil wars in sub-Saharan Africa, a region notorious for its weak state capacity and limited legal infrastructure." Kalyvas and Balcells 2010;Kalyvas 2003Kalyvas , 2005Raeymaekers 2005;Salehyan 2009;Staniland 2012Staniland , 2014 See, e.g., Brass 1997;Hazen 2013;Mampilly 2011;Menkhaus 2007;Raeymaekers, Menkhaus, and Vlassenroot 2008. Kalyvas and Balcells 2010 1969.…”
Section: Resolving Civil Conflict In the Midst Of Uncertaintymentioning
confidence: 99%
“…Contemporary contexts of mass violence evolve in a landscape of long-term and multifaceted conflicts, extreme violence and state fragility (for an overview, see Karstedt 2013a). The majority of mass killings since World War II have been part of civil wars and ethnic conflicts (Kalyvas and Balcells 2010). These conflicts typically occur below the level of the nation-state and independent of its boundaries.…”
Section: Contemporary Landscapes Of Mass Violence and Atrocity Crimesmentioning
confidence: 99%